The Irish economy during the century after partition - Cormac Ó Gráda; Kevin Hjortshøj O'Rourke (University College Dublin, UCD Centre for Economic Research, 2021)
We provide a centennial overview of the Irish economy in the one hundred years following partition and independence. A comparative perspective allows us to distinguish between those aspects of Irish policies and performance that were unique to the country, and those which mirrored developments elsewhere. While Irish performance was typical in the long run, the country under-performed prior to the mid-1980s and overperformed for the rest of the twentieth century. Real growth after 2000 was slow. The mainly chronological narrative highlights the roles of convergence forces, trade and industrial policy, and monetary and fiscal policy. While the focus is mostly on the south of the island, we also survey the Northern Irish experience during this period.
hdl:10197/12104
Keywords: N14; 330; Ireland; economic growth; living standards; trade policy; crises